2008
DOI: 10.1088/1475-7516/2008/04/029
|View full text |Cite
|
Sign up to set email alerts
|

Probing new physics with long-lived charged particles produced by atmospheric and astrophysical neutrinos

Abstract: As suggested by some extensions of the standard model of particle

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 105 publications
0
38
0
Order By: Relevance
“…We also discuss uncertainties in the QCD approach, and compare our results with the uncertainty band of Ref. [6] in Section IV.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…We also discuss uncertainties in the QCD approach, and compare our results with the uncertainty band of Ref. [6] in Section IV.…”
Section: Introductionmentioning
confidence: 86%
“…In Ref. [6], Ando et al have suggested that the high energy atmospheric neutrino flux may be large enough to produce quasistable charged particles that are potentially detectable in the IceCube [7] neutrino detector. As a background to high energy sources or as a flux to produce exotic particles in the Earth, it is useful to re-evaluate the high energy component of the atmospheric neutrino flux.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SUSY theories where the LSP is the gravitino and the next-to-LSP (NLSP) is a longlived charged particle (typically a slepton), e.g. in gauge mediation models [138], the diffuse flux of UHE neutrinos interacting with the Earth could produce pairs of slepton NLSPs which could be detected in neutrino telescopes [70][71][72][73][74][75]. The basic process involves the tchannel production of a slepton and a squark via gaugino exchange, see Fig.…”
Section: Long-lived Charged Sparticlesmentioning
confidence: 99%
“…The presence of such particles is predicted in many notable models beyond the standard model, although its identity depends on the models one assumes. CHAMP hunting is indeed one of the major issues of the high energy experiments, and its collider phenomenology is enthusiastically studied [1][2][3][4][5][6][7][8][9][10][11][12][13][14]; it also motivates other researches including neutrino telescope observations [15][16][17] and cosmology [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%